2016
DOI: 10.3389/fpls.2016.01534
|View full text |Cite
|
Sign up to set email alerts
|

Drought-Tolerant Corn Hybrids Yield More in Drought-Stressed Environments with No Penalty in Non-stressed Environments

Abstract: The potential benefit of drought-tolerant (DT) corn (Zea mays L.) hybrids may depend on drought intensity, duration, crop growth stage (timing), and the array of drought tolerance mechanisms present in selected hybrids. We hypothesized that corn hybrids containing DT traits would produce more consistent yields compared to non-DT hybrids in the presence of drought stress. The objective of this study was to define types of production environments where DT hybrids have a yield advantage compared to non-DT hybrids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 27 publications
7
53
0
Order By: Relevance
“…Crop breeders have made efforts to develop drought-tolerant crops such as corn (Zea mays L.), bread wheat (Triticum aestivum L.), cotton (Gossypium hirsutum L.), soya bean and rice (Oryza sativa L.) (Basal, Smith, Thaxton, & Hemphill, 2005;Bolanos & Edmeades, 1996;Dhanda, Sethi, & Behl, 2004;Sapra & Anaele, 1991;Sloane, Patterson, & Carter, 1990 ). Commercially available drought-tolerant corn hybrids were recently released by DuPont Pioneer (AQUAmax TM ), Syngenta (Artesian TM ) and Monsanto (DroughtGard TM ) (Adee, Roozeboom, Balboa, Schlegel, & Ciampitti, 2016). Among a range of environments differing in evaporative demand and drought, there was a yield advantage of AQUAmax and DroughtGard hybrids over the non-drought-tolerant hybrids that increased as drought severity increased, but there was no difference in yield between drought-tolerant and non-drought-tolerant hybrids in the absence of stress (Adee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Crop breeders have made efforts to develop drought-tolerant crops such as corn (Zea mays L.), bread wheat (Triticum aestivum L.), cotton (Gossypium hirsutum L.), soya bean and rice (Oryza sativa L.) (Basal, Smith, Thaxton, & Hemphill, 2005;Bolanos & Edmeades, 1996;Dhanda, Sethi, & Behl, 2004;Sapra & Anaele, 1991;Sloane, Patterson, & Carter, 1990 ). Commercially available drought-tolerant corn hybrids were recently released by DuPont Pioneer (AQUAmax TM ), Syngenta (Artesian TM ) and Monsanto (DroughtGard TM ) (Adee, Roozeboom, Balboa, Schlegel, & Ciampitti, 2016). Among a range of environments differing in evaporative demand and drought, there was a yield advantage of AQUAmax and DroughtGard hybrids over the non-drought-tolerant hybrids that increased as drought severity increased, but there was no difference in yield between drought-tolerant and non-drought-tolerant hybrids in the absence of stress (Adee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To classify 2,452 corn hybrids as either tolerant or susceptible to drought stress, heat stress, and combined drought and heat stress, we performed regression analysis on the yield of hybrids and extracted stress metrics. We conducted linear regression of yield of hybrid against each stress, and classified the hybrid based on the slope of the regression line, since the slope of the regression line indicates the yield adaptability of the hybrid (Adee et al, 2016). The intuition behind this approach is that if a hybrid is tolerant against a type of stress, then the slope of the regression line should be a positive value or a small negative value.…”
Section: Hybrid Stress Classification Methodsmentioning
confidence: 99%
“…To improve the corn performance under environmental stresses, seed companies have started developing stress-tolerant corn hybrids to alleviate the negative effects of drought and heat stress. Drought-tolerant (DT) hybrids have been developed through traditional plant breeding such as Pioneer Optimum AQUAmax TM and Syngenta Artesian TM , which yielded 5% to 7% more than non-DT hybrids in high stress environments, while maintaining a comparable yield potential in high yielding environments (Adee et al, 2016). Chen et al (2012) identified some heat tolerant corn inbred lines that demonstrated an enhanced tolerance to elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7% yield gains are obtained for these deregulated hybrid maize, which has also been approved for import to China since 2013, as MON7460. No performance penalty was found in non-stressed environments (58,59). The Genuity DroughtGard series of hybrids (60) also include combinations of stacked genes, including resistance to particular herbicides and potentially pests such as the European corn borer, for particular settings (61).…”
Section: Drought Tolerance and Water Use Efficiencymentioning
confidence: 99%